KOMUNIKASI INTERPERSONAL PEGAWAI DI DINAS PEMUDA DAN OLAHRAGA PROVINSI SUMATERA BARAT - Eka Nopera (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about interpersonal communication. The population is 124 employee and the sample is 59 people that taken by proportional random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are interpersonal communication in Dinas Pemuda dan Olahraga Provinsi Sumatera Barat. Key word :Interpersonal Commucation